2019
DOI: 10.1144/sp481-2017-172
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of lithosphere structure and characterization of the Moho geometry under the Himalaya–Karakoram–Tibet collision zone using surface-wave tomography

Abstract: Group velocities for a period range of 6–60 s for the fundamental mode of the Rayleigh wave passing across the Himalaya–Karakoram–Tibet orogen are used to delineate the structure of the upper lithosphere using the data from 35 broadband seismic stations. 2D tomography velocity maps of group velocities were obtained at grids of 1° separation. Redefined local dispersion curves are inverted non-linearly to obtain 1D velocity models and to construct a 3D image of the S-wave structure down to a depth of 90 km.The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 98 publications
2
20
0
Order By: Relevance
“…A similar midcrustal low velocity layer is observed beneath both the Lhasa Terrane and the Tethyan Himalayas, which is uninterrupted by the Karakoram Fault, indicating that the fault does not cut through the entire crust (shallow fault) (Gilligan et al, 2015). Both the studies (Kumar et al, 2017(Kumar et al, , 2019 indicated high velocities in the deeper part in the south. While the former interpreted the high velocities in terms of dense and cold lower crust and uppermost mantle of the Indian plate, the latter attributed it to lateral heterogeneity of the crust and strong anisotropy in the lower crust beneath the frontal Himalayan region (western Himalaya) due to development of preferably oriented folds/ faults/fractures and reorientation of crystals as a consequence of the ongoing deformation caused by the continent-continent collision.…”
Section: Deccan Volcanic Province (Dvp)mentioning
confidence: 56%
See 3 more Smart Citations
“…A similar midcrustal low velocity layer is observed beneath both the Lhasa Terrane and the Tethyan Himalayas, which is uninterrupted by the Karakoram Fault, indicating that the fault does not cut through the entire crust (shallow fault) (Gilligan et al, 2015). Both the studies (Kumar et al, 2017(Kumar et al, , 2019 indicated high velocities in the deeper part in the south. While the former interpreted the high velocities in terms of dense and cold lower crust and uppermost mantle of the Indian plate, the latter attributed it to lateral heterogeneity of the crust and strong anisotropy in the lower crust beneath the frontal Himalayan region (western Himalaya) due to development of preferably oriented folds/ faults/fractures and reorientation of crystals as a consequence of the ongoing deformation caused by the continent-continent collision.…”
Section: Deccan Volcanic Province (Dvp)mentioning
confidence: 56%
“…The dipping geometry of the Indian plate is captured by a gradual increase in both the Conrad and Moho depths (Kumar et al, 2017). This was subsequently corroborated by the NE-dipping Moho inferred by Kumar et al (2019), studying the Rayleigh wave group velocities in the period range of 6-60 s across the Himalaya-Karakoram-Tibet. The Moho depth increases from ~40 km beneath the frontal part of the Himalaya to ~70-80 km beneath the collision zone and shallows down substantially beneath the Tarim basin.…”
Section: Deccan Volcanic Province (Dvp)mentioning
confidence: 69%
See 2 more Smart Citations
“…The data recorded during a period of three days before and after the earthquakes quantify the displacement of the GNSS station from its original position. Kumar et al (2019) delineate the structure of the upper lithosphere using seismic data collected from 35 broadband seismic stations located across the HKT orogen. The results suggest a NE-dipping Moho, increasing in depth from c. 40 km beneath the frontal part of the Himalaya down to c. 70-80 km beneath the collision zone, then shallowing substantially beneath the Tarim basin.…”
mentioning
confidence: 99%